Forest Diseases in Brazil: Status and Management - Furtado, Edson Luiz [UNESP]; de Jesus Junior, Waldir Cintra; Moraes, Willian Bucker (Springer Nature, 2020)
Brazil has an area of 851.6 million ha, of which over 477 million ha is covered with natural forest and other 7.84 million ha has commercial forest plantations. The latter are dominated by non-native species: eucalypts, pines, teaks, acacia, poplars, gmelina, and African mahogany, which occupy 96% of forestry areas, while native species like rubber tree (Hevea spp.), “cuiabano” pine (Schizolobium amazonicum), and swamp cedar (Calophyllum brasiliense) occupy 4%. Surveys conducted over the last two decades have shown important diseases and damage for cultivated species: Eucalyptus, Austropuccinia psidii (myrtaceous rust); Hevea, Microcyclus ulei (South American leaf blight). In this chapter you can obtain more details about the management of these diseases so dangerous to the world.
Keywords: Exotic species; Host range expansions; Host tracking; Management; Native species; Pathogenic fungi